Smart Dielectric Barrier Discharge Plasma Decontamination: Spatially Targeted Decontamination With Actuated Ozone Distribution - Choudhury, Bhaswati; Portugal, Sherlie; Roy, Subrata; Mastro, Emma; Johnson, Judith A. (Frontiers in Physics, 2022)
This study introduces spatially targeted decontamination using a synergistic combination of Dielectric Barrier Discharge (DBD) flow actuation and ozone generation. Here, we relate spatial distribution of local microbial decontaminations in an enclosure to that of local ozone concentrations caused by DBD ozone generation and flow actuation, using two reactors with contrasting flow actuation, the Fan and Comb reactors, run at equal power of 1+0.03W for 3.5 minutes. Deviations in ozone concentrations and reductions of Escherichia coli on contaminated coupons over two planes were used to quantify the utilization capacity of generated ozone to simultaneously disinfect regions of a surface placed in the planes. Results show that uniform ozone consumption by a contaminated target i.e., targeted decontamination, lowers ozone requirements, exposure times and reactor energy consumption for its disinfection. Further, a significant positive correlation was found between local decontamination and ozone concentrations with Pearson’s correlation, ρ (34) = 0.64; p<0.001. Simulated ozone distribution using an experiment integrated simulation method, governed by DBD reactor geometry induced flow actuation and ozone reaction rates, is also presented for predicting DBD actuated spatial decontamination distribution. Our study shows an innovative approach of applying DBD plasma reactors for decontamination using flow actuation and ozone generation to achieve targeted killing with maximized ozone utilization lowering overall ozone dosage requirements, energy requirements, and exposure times.